Miniatured computed tomography system and calibration - Pititheerapab, Y.; Chanwimalueang, T.; Pintavirooj, C.; Tosranon, P. (My University, 2006)
In this paper, we focus on a miniature computed tomographic system with application in 3D modelling of bony structure of a small animal. Our system consists of an x-ray source, a rotating platform and an x-ray array detector unit. The rotating platform is controlled by a personal computer which can rotate the sitting object to arbitrary angle. The x-ray array detector is used to capture the 2D x-ray signal that traversing the object placed on the platform. The x-ray detector is an image intensifier tube of which the 2D image is coupled to the computer via a CCD camera. Feldkamp Conebeam technique is engaged for reconstructing tomograms due to its simplicity. Volume rendering technique together with the shading effects is performed on a stack of cross-sectional image to realize the data into 3D visualization. The algorithms are applied to the practical situation where a series of x-ray radiographs of an animal's bone are collected from the system. The 3D modelling of such bone is performed on the cross-sectional images reconstructed with Feldkamp Conebeam. The results are very satisfactory. © 2006 IEEE.
Keywords: Backprojection; CT; Feldkamp; Image reconstruction; Volume rendering